2007
DOI: 10.1007/s10549-007-9610-z
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine in the management of metastatic breast cancer: a systematic review

Abstract: Available data do not support the acceptance of gemcitabine as a standard therapeutic option in women with metastatic breast cancer in the third-line or greater setting, nor should it be considered as first-line therapy in anthracycline naïve women. Gemcitabine appears to be most effective when administered with a taxane (docetaxel/paclitaxel) in the first- or second-line setting, with gemcitabine/taxane combinations representing a viable alternative to currently accepted taxane combinations such as capecitabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 65 publications
2
41
0
Order By: Relevance
“…Gemcitabine, a pyrimidine antimetabolite, has potential for combination therapy because of its unique mechanism of action and non-overlapping toxicity profile with nonanthracycline treatments [6][7][8]. Two randomized controlled trials have demonstrated the efficacy of gemcitabine/taxane combinations as first-line and/or second-line treatment for metastatic breast cancer [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Gemcitabine, a pyrimidine antimetabolite, has potential for combination therapy because of its unique mechanism of action and non-overlapping toxicity profile with nonanthracycline treatments [6][7][8]. Two randomized controlled trials have demonstrated the efficacy of gemcitabine/taxane combinations as first-line and/or second-line treatment for metastatic breast cancer [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common malignant tumor among women in many advanced countries [1,2]. About 200,000 new cases of breast cancer were diagnosed in USA and among them, more than 40,000 cases of death occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Further preclinical testing of gemcitabine in NHL cell lines has demonstrated encouraging activity, similar to that observed with ARA-C and 2-CDA [12]. Gemcitabine has been shown to exert anti-tumor effects against several solid tumors, including pancreatic, ovarian, lung, breast, and bladder tumors [13][14][15]. In clinical trials, gemcitabine has been shown to evidence significant clinical activity in relapsed patients with both Hodgkin's disease and aggressive NHL, generating improved response rates [16][17][18].…”
Section: Introductionmentioning
confidence: 85%
“…Gemcitabine is an analogue of deoxycytidine, with activity against several solid tumors-including pancreatic, lung, and breast cancer [13][14][15]. It is well tolerated, with minimal hematologic and non-hematologic toxicities.…”
Section: Discussionmentioning
confidence: 99%